Simbolisme #bravepink dan #herogreen dalam Kerangka COLOR-BASED ACTIVISM di Era Media Sosial - Satria Kamal Akhmad; Dinia Saridewi (ALAMTARA, 2025)
This study examines the use of the color symbols #bravepink and #herogreen in Indonesian digital demonstrations after August 25, 2025, as a form of affect-based digital activism. The research aims to analyze how these symbols are interpreted, mobilized, and employed to build collective solidarity on social media. Using a case study design with purposive sampling, the study includes 212 public accounts on Twitter/X, Instagram, TikTok, and Facebook that met the criteria of interaction level and hashtag use. Data were collected through BrandMention and Talkwalker and analyzed using Kress and van Leeuwen’s social semiotics. The results show that #bravepink demonstrated higher viral reach, while #herogreen achieved stronger public acceptance and moral value associations. Both symbols generated high emotional engagement, particularly among young women. These findings highlight color as a primary medium in digital emotional politics and propose color-based activism as a theoretical contribution for understanding visual symbols in contemporary social movements.